1996
DOI: 10.1111/j.1600-0714.1996.tb01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of p16/CDKN2, p53 and ras genes in oral squamous cell carcinomas and premalignant lesions

Abstract: Exons 1-3 of the p16/CDKN2 gene, exons 4-9 of the p53 gene and exons 1 and 2 of H-, K- and N-ras genes were screened for mutations by a combination of immunohistochemistry and single-strand conformational polymorphism (SSCP) analyses of polymerase chain reaction products from human surgical samples of both frank oral squamous cell carcinomas and premalignant lesions. The samples included 20 squamous cell carcinomas, 10 epithelial dysplasias and 10 epithelial hyperplasias. No identifiable gene mutations were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
(4 reference statements)
3
26
1
3
Order By: Relevance
“…A prevalence of p16 alterations, ranging from 25% to 83%, has been reported in head and neck SCC [5,6,8,10,21,27,30]. The variable findings may be attributable to different patient populations and varying methodologies used for analysis.…”
Section: Discussionmentioning
confidence: 98%
“…A prevalence of p16 alterations, ranging from 25% to 83%, has been reported in head and neck SCC [5,6,8,10,21,27,30]. The variable findings may be attributable to different patient populations and varying methodologies used for analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Functional loss of tumor suppressor genes is supposed to be one of the most common genetic alterations in the oral carcinogenesis. 13,15,17 El-Naggar et al showed that the most likely chromosomal region associated with early development of head and neck squamous carcinoma was 9p21. 12 In recent studies, 9p and/or 3p were reported as the essential step in head and neck carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The histology of advanced colonic cancers could not be divided into the tow types, although K-ras point mutations frequently occurred in the former and rarely in the latter [24]. K-ras point mutations have been shown to be less frequent in oral SCCs [25,26].…”
Section: Discussionmentioning
confidence: 99%